2018
DOI: 10.1016/s2214-109x(18)30383-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ten-valent pneumococcal conjugate vaccine introduction on pneumococcal carriage in Fiji: results from four annual cross-sectional carriage surveys

Abstract: SummaryBackgroundThe indirect effects of pneumococcal conjugate vaccines (PCVs) are mediated through reductions in carriage of vaccine serotypes. Data on PCVs in Asia and the Pacific are scarce. Fiji introduced the ten-valent PCV (PCV10) in 2012, with a schedule consisting of three priming doses at 6, 10, and 14 weeks of age and no booster dose (3 + 0 schedule) without catch-up. We investigated the effects of PCV10 introduction using cross-sectional nasopharyngeal carriage surveys.MethodsWe did four annual car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 35 publications
(50 reference statements)
4
57
0
1
Order By: Relevance
“…Findings from previous epidemiological studies have proved inconclusive regarding the impact of PCVs on pneumococcal colonisation density [5], [6], [7], [8]. The advantage of the EHPC model is the ability to study colonisation dynamics in a controlled manner, clarifying causality and eliminating the effect of many confounding factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings from previous epidemiological studies have proved inconclusive regarding the impact of PCVs on pneumococcal colonisation density [5], [6], [7], [8]. The advantage of the EHPC model is the ability to study colonisation dynamics in a controlled manner, clarifying causality and eliminating the effect of many confounding factors.…”
Section: Discussionmentioning
confidence: 99%
“…Disease and transmission prevention requires interruption of colonisation [3]. Numerous studies have reported a reduction in vaccine-type (VT) pneumococcal colonisation acquisition after PCV vaccination, however, the impact of PCVs on pneumococcal colonisation density is less clear [5], [6], [7], [8]. Studies have shown that vaccination with PCV reduces colonisation densities with VT serotypes when comparing to control vaccines [5].…”
Section: Introductionmentioning
confidence: 99%
“…An NP and OP swab were collected from 250 adult caregivers of children (adult caregivers) in 2012 as part of the Fiji New Vaccine Evaluation Project, described previously ( 22 ); see Table S1 for study participant characteristics. In brief, NP and OP specimens were collected concurrently by the same personnel using flocked nylon swabs ( 11 , 12 ) and were otherwise handled in the same manner.…”
Section: Methodsmentioning
confidence: 99%
“…DNA was extracted from 100 μl of STGG sample as previously described ( 22 ). Each extraction run contained approximately equal numbers of NP and OP samples and included STGG extraction controls that were checked for pneumococcal contamination using lytA qPCR.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation